KONTRIBUSI APRESIASI SISWA TENTANG PEMBELAJARAN SEJARAH, PEMAHAMAN IDEOLOGI PANCASILA, PEMAHAMAN NILAI- NILAI AGAMA TERHADAP SIKAP NASIONALISME - Mohamad Naim (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2020)
Efforts to develop an attiude of nationalism in students within the multicultural life of the Indonesian people is not easy. There should be a strategic move. Integration curriculum between History, Civics, and Religion are needed. The values of teaching history contained within historical events can evoke nationalism. An understanding of Pancasila through Civics curricuum as a guide to behave in society, nation, and state can strengthen the love of the nation. An understanding of religious values can be the basis of the rule of truth, preserving the integrity of the state or nation and nationalism. Students' appreciation of the history of learning, understanding of Pancasila and religious values can improve the attitude of nationalism.